Jaringan Kerjasama Perpustakaan Perguruan Tinggi - Elisa Ananda Br Hutapepa; ndah Lestari; Umar Ariansyah Siregar; Febri Dwi Sasmita; Yusniah Yusniah (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
Collaboration between libraries is carried out to provide the best customer-focused library services. This library partnership aims to increase activity levels across multiple sources while improving user and technical services. Creating a cooperative strategy involves using policy strategies, HR, correlation, resource sharing, and information technology. The implementation of this work was constrained and supported by several circumstances. This is made possible by various elements, including user demands, technological advances, and extended use. Cooperation is hampered by geographical distance, spatial constraints, and time. Keywords: Cooperation; Library; College